SPONTANEOUS CONSOLIDATION OF SCAPHOID NONUNION IN A CHILD - Manak, Pavel; Drac, Pavel; Paucek, Boris (Biomedical papers, 2008)
BACKGROUND: Scaphoid nonunion is very rare in childhood.CASE REPORT: A 14 year old boy with scaphoid nonunion confirmed with CT did not past scheduled surgery. In spite of the short period of immobilisation union occurred and two years after the injury he was completely asymptomatic.CONCLUSIONS: We suspect that injury to the scaphoid, in this case may have accelerated the union shortly before the end of ossification.
Keywords: Childhood scaphoid nonunion/Spontaneous consolidation/Conservative treatment/Computed tomography